2014
DOI: 10.1093/ofid/ofu027
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Activation and Repair During Hantavirus Infection: Association with Disease Outcome

Abstract: Background. Endothelial activation and dysfunction play a central role in the pathogenesis of sepsis and viral hemorrhagic fevers. Hantaviral disease is a viral hemorrhagic fever and is characterized by capillary dysfunction, although the underlying mechanisms for hantaviral disease are not fully elucidated.Methods. The temporal course of endothelial activation and repair were analyzed during Puumala hantavirus infection and associated with disease outcome and a marker for hypoxia, insulin-like growth factor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 47 publications
1
37
0
1
Order By: Relevance
“…In adults with sepsis, circulating glycosaminoglycans including HA, was increased in patients with septic shock and was highest in those with a fatal outcome25. Adults with Pumala hantavirus infection had increased syndecan-1 (a marker of endothelial glycocalyx degradation), which was associated with disease severity26. In Vietnamese children with DSS, there was a selective increase in the renal clearance of glycosaminoglycans with increased urinary excretion of HS but not chondroitin-4-sulphate or chondroitin-6-sulphate16.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with sepsis, circulating glycosaminoglycans including HA, was increased in patients with septic shock and was highest in those with a fatal outcome25. Adults with Pumala hantavirus infection had increased syndecan-1 (a marker of endothelial glycocalyx degradation), which was associated with disease severity26. In Vietnamese children with DSS, there was a selective increase in the renal clearance of glycosaminoglycans with increased urinary excretion of HS but not chondroitin-4-sulphate or chondroitin-6-sulphate16.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that are responsible for the more severe and protracted course of DOBV-Sochi infection are not completely understood. Previous studies have demonstrated a role of endothelial activation and repair in the clinical course of PUUV infection [30, 37]. The normalization of clinical parameters has been paralleled to the mobilization of endothelial progenitor cells.…”
Section: Discussionmentioning
confidence: 91%
“…[27,32] Neither seems enhanced clearance or pooling of platelets in the enlarged spleen to be involved, as indicated by a previously recorded lack of association of thrombocytopenia and spleen size in PUUV induced HFRS. [33] Endothelial activation markers associate with thrombocytopenia [34] and pathogenic hantaviruses are known to direct the adherence of quiescent platelets through b3-integrin to the surface of infected endothelial cells [35] and specifically to PUUV particles. [36] The adherence of platelets may result in altered platelet activation and decreased circulating platelet count as well as a loss of vascular integrity.…”
Section: Discussionmentioning
confidence: 99%